Larval locomotion behavior in three species of Drosophila - Alam, Mohammad Shamimul; Poly, Farjana Sultana; Rahman, Sadniman; Begum, Rowshan Ara (Bangladesh Journal of Zoology, 2019)
Abstract not available Bangladesh J. Zool. 47(2): 367-371, 2019